Transferring Digital Artworks on Online Market Platforms - Juhász, Ágnes; Sztermen, Lili Orsolya (Public Governance, Administration and Finances Law Review, 2024)
By writing this paper, the authors intended to answer questions raised by the transfer of digital artworks in the online space. At the beginning of the study, the basic expressions, including NFT digital artwork, will be explained. Then, it will be examined how these new forms of artwork can be treated by civil law. Although NFTs change hands daily, their legal nature, i.e. if they shall be deemed as things in the civil law sense, is unclear. If NFTs are treated as things, they can be a subject of ownership, and the provisions on the transfer of ownership rights shall be applied, which raises several further questions. According to another approach, NFTs embody the right to dispose, while there are other opinions as to which NFTs, following the model of bank account money, shall be deemed as claims facilitating the application of the provisions of the law of obligations. After reviewing the different approaches to the legal nature of NFTs, features of online auctions of NFT artworks will be introduced. Then, it will be examined if the platforms enabling online auctions fall under the scope of the recently adopted Digital Market Act and if so, which rules of the Act are applicable for them.